2000
DOI: 10.1038/35006081
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 polymorphisms associated with increased risk of gastric cancer

Abstract: Charles S., "Interleukin-1 polymorphisms associated with increased risk of gastric cancer" (2000). To evaluate dopaminergic cells of the dorsomedial cluster by tyrosine hydroxylase immunostaining, serial 4-mm sections were cut to include the entire brain. Immunopositive cells at the level of the giant interneuron commissure, posterior to the fan-shaped body, were counted in well oriented frontal sections at 1, 10, 30 and 60 days. At 1 day all control and experimental sections contained four or ®ve cells in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

91
1,660
33
45

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,130 publications
(1,847 citation statements)
references
References 28 publications
91
1,660
33
45
Order By: Relevance
“…42,44 Our preliminary results represent a new approach for the study of LD of the 2q14 band, and the LD patterns observed in other studies are easier to understand given the LDU map we have constructed. We are aware that the LD map here presented is based on a few polymorphisms; however, we are reassured on the reliability of our results because Figure 3 shows a pattern closely similar to an independent LDU map of this region constructed from data used in a study of asthma 45 based on 93 SNPs (one SNP every 5.3 kb) covering a region spanning 490.25 kb.…”
Section: Discussionmentioning
confidence: 73%
“…42,44 Our preliminary results represent a new approach for the study of LD of the 2q14 band, and the LD patterns observed in other studies are easier to understand given the LDU map we have constructed. We are aware that the LD map here presented is based on a few polymorphisms; however, we are reassured on the reliability of our results because Figure 3 shows a pattern closely similar to an independent LDU map of this region constructed from data used in a study of asthma 45 based on 93 SNPs (one SNP every 5.3 kb) covering a region spanning 490.25 kb.…”
Section: Discussionmentioning
confidence: 73%
“…Of the remaining 38 publications, three were eliminated, due to reporting duplicate data 17, 18, 19. Ultimately, 37 studies from 35 publications 6, 10, 14, 15, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50 including 6108 cases and 8980 controls were included in the meta‐analysis (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…transcription factors). As an example, lipopolysaccharide stimulation induced approximately a fivefold increase in the formation of DNA–protein complex in the presence of IL‐1B 31T oligonucleotide, while no effect on the IL‐1B 31C oligonucleotide was observed 6. Accordingly, IL‐1B 31C>T polymorphism has been shown to influence IL1β production, with variant T allele associated with enhanced expression of IL1β in comparison with wild‐type C allele 8, 9, 10.…”
Section: Introductionmentioning
confidence: 98%
“…These two polymorphisms are in significant LD (see Figure 3). The IL1B À31T allele creates a TATA box, which has been shown to bind TATA-binding protein (TBP), 41 whereas the IL1B À31C allele does not. It has been suggested that the strongly linked IL1B À31T and the IL1B À511G alleles may be associated with higher T on IL1B coding strand.…”
Section: Resultsmentioning
confidence: 99%
“…Interleukin-1 gene cluster associated with OA AJP Smith et al levels of gene expression than the IL1B À31C and IL1B À511A alleles: 41,42 we are currently investigating this possibility. This could represent a partial functional explanation for the association of the risk haplotype (2C-CTG-1TT) with knee OA, since this haplotype contains the IL1B À31T and IL1B À511G genotypes, is TATA-box positive, and may be associated with highlevel expression of IL-1b (a potent mediator of inflammation in OA joints).…”
Section: Resultsmentioning
confidence: 99%